Systematic Literature Reviews : Analisis Pajak, Tunneling Insentive dan Exchange Rate Terhadap Keputusan Tranfer Pricing Perusahaan - Syafira Salsabilla; Linggar Sekar Kemuning; Dien Noviany Rahmatika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Transfer pricing is a pricing policy for transactions between parties with a special relationship. However, multinational companies often use transfer pricing to reduce the overall taxation of the multinational group. The purpose of this study is to review the literature using the systematic literature review (SLR) method, considering various aspects such as the impact of taxes, tunneling incentives and exchange rates on transfer pricing decisions of manufacturing companies discussed in previous studies. 60 journals from different sources were used in this study. The method used in this study is the SLR method (Systematic Literature Review Method). This study was conducted over several years to provide a performance evaluation. Therefore, this paper conducted a systematic literature review to find out which methods were used to analyze the impact of taxes, tunneling incentives and exchange rates on transfer pricing decisions of manufacturing companies.